Writings, Offices and Power. The Professional Activity and Documentary Production of a Valley Notary in the Institutional Construction of the Confederates ‘Baliaggi Italiani’ (Late Fifteenth-Early Sixteenth Century) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
In the period between 1439 and 1521 the coalition of Swiss rural communities and towns conquered eight districts in the alpine valleys along the St. Gotthardroute, which had been part of the Milanese duchy since its rise in the 14th century. The establishment of a new regime in this region was the result of a complex negotiation process, because the linguistic, legai, and political cultures of the new rulers and their subjects were fundamentally different. The paper focuses on a public notary of the Leventina valley named Pietro Pedruzzi, by observing his activity as a charter writer as well as a public official and as an intermediary between the conquerors and the local community members. he createci severa! new forms of documents combining elements of the notarial «instrumenta» and the sealed charters, which were functional both to the administration of the territories and to the representation of the new rulers' power.DOI 10.17464/9788867743308
Keywords: Public notaries; local governance; diplomatics; languages and cultures; Duchy of Milan; Swiss Confederation; Alpine valleys